2010
DOI: 10.22358/jafs/66272/2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of encapsulated and non-encapsulated compound acidifiers on gastrointestinal pH and intestinal morphology and function in weaning piglets

Abstract: The experiment was conducted to study the effects of the addition of encapsulated and nonencapsulated compound acidifiers in a diet based on maize-soyabean meal-extruded soyabean on gastrointestinal pH, growth performance, villus height and crypt depth of jejunum, intestinal digestive enzymes activities, microbial population and intestinal mucosal secretory immunoglobulin A in weaning piglets. Sixty-four 28-day-old, crossbred piglets (LandracexLarge White), weighing an average of 7.00±0.10 kg, were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Many studies (Tilman and Eckel, 1998;Tung and Pettigrew, 2003;Jia et al, 2010) supported the results of average daily gain (ADG), specific growth rate (SGR) and survival rate (SR) which were significantly higher in T2 group compared to T1 and T3 with the values of T1 are significantly higher than that of T3 and these studies concluded that, using acidifiers (0.2, 0.3 or 0.5%) significantly (P<0.05) improved BW and WG of O. niloticus (Ramli et al, 2005). In a recent study, the supplementation of the basal diet by 1% Ca-lactate significantly (P<0.001) improved BW, BL, WG and SGR of Nile tilapia, O. niloticus (Mogheth, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies (Tilman and Eckel, 1998;Tung and Pettigrew, 2003;Jia et al, 2010) supported the results of average daily gain (ADG), specific growth rate (SGR) and survival rate (SR) which were significantly higher in T2 group compared to T1 and T3 with the values of T1 are significantly higher than that of T3 and these studies concluded that, using acidifiers (0.2, 0.3 or 0.5%) significantly (P<0.05) improved BW and WG of O. niloticus (Ramli et al, 2005). In a recent study, the supplementation of the basal diet by 1% Ca-lactate significantly (P<0.001) improved BW, BL, WG and SGR of Nile tilapia, O. niloticus (Mogheth, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal VH and CD are important indicators of the digestive health of the animal and are directly related to the absorptive capacity of the mucous membrane (Buddle and Bolton, 1992;Jia et al, 2010). Morphological changes in the small intestine, such as shorter villi and deeper crypts, have been related to the presence of toxins, which are primarily related to a reduced feed intake (Gislason et al, 1993;Pluske et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia of the enteric canal can cause epithelial shedding (Rivera et al, 2011), proceeding to shortened villus height and deeper crypt depth. Jia et al (2010) found that both villus height and crypt depth are important indicators of the digestive health of poultry and are directly related to the absorptive capacity of the mucous membrane. In addition, higher villus-to-crypt ratios suggest higher digestive and absorptive capacities in the jejunum (Xu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%